DEPENDENCE OF ECONOMIC SAFETY OF THE RUSSIAN SUBJECTS ON THEIR FOREIGN TRADE - Glechikova, Natalia; Seriogin, Aleksandr; Reva, Alla (Revista Inclusiones, 2020)
The research objective is to study the regional aspect of economic safety in relation with the overall economic development of the Russian federal districts and Russia in general. The main tasks are to determine the indices of economic safety of the regions and federal districts and to graphically show the dependence of economic safety on the foreign trade coefficient, while the regional economy reduces its dependence on external and internal threats. As a result, it is necessary to increase the level of managing the country’s economy to maintain a certain macroeconomic balance, taking into account the chosen criteria of economic transformations in the society.